Mu and Delta opioid receptors activate the same G proteins in human neuroblastoma SH-SY5Y cells - Alt, A (2002)
1. There is evidence for interactions between mu and delta opioid systems both in vitro and in vivo. This work examines the hypothesis that interaction between these two receptors can occur intracellularly at the level of G protein in human neuroblastoma SH-SY5Y cells. 2. The [(35)S]GTPγS binding assay was used to measure G protein activation following agonist occupation of opioid receptors. The agonists DAMGO (EC(50), 45 nM) and SNC80 (EC(50), 32 nM) were found to be completely selective for stimulation of [(35)S]-GTPγS binding through mu and delta opioid receptors respectively. Maximal stimulation of [(35)S]-GTPγS binding produced by SNC80 was 57% of that seen with DAMGO. When combined with a maximally effective concentration of DAMGO, SNC80 caused no additional [(35)S]-GTPγS binding. This effect was also seen when measured at the level of adenylyl cyclase. 3. Receptor activation increased the dissociation of pre-bound [(35)S]-GTPγS. In addition, the delta agonist SNC80 promoted the dissociation of [(35)S]-GTPγS from G proteins initially labelled using the mu agonist DAMGO. Conversely, DAMGO promoted the dissociation of [(35)S]-GTPγS from G proteins initially labelled using SNC80. 4. Tolerance to DAMGO and SNC80 in membranes from cells exposed to agonist for 18 h was homologous and there was no evidence for alteration in G protein activity. 5. The findings support the hypothesis that mu- and delta-opioid receptors share a common G protein pool, possibly through a close organization of the two receptors and G protein at the plasma membrane.